2002
DOI: 10.1063/1.1498876
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric measurement to probe electron ordering and electron-spin interaction

Abstract: Here we found that dielectric measurement can be a sensitive probe to detect the behavior of electrons and electron-spin interaction in a strongly electron-correlated system. The CuO single crystal samples with and without excess holes were investigated by dielectric measurements in combination with magnetic susceptibility measurement. Only for the semiconducting single crystal with holes was dynamic dielectric relaxation with prominent frequency dispersion and large dielectric constants observed, suggesting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 27 publications
5
31
0
Order By: Relevance
“…This technique has been proved to be a sensitive probe to detect the electron behavior in strongly electron-correlated high-temperature superconducting cuprate systems. 13,14 It is, therefore, expected that the dielectric investigations of MgB 2 may shed some lights on the intergrain properties. Unfortunately, most of the existing reports on dielectric properties of MgB 2 were measured on microwave and optical frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been proved to be a sensitive probe to detect the electron behavior in strongly electron-correlated high-temperature superconducting cuprate systems. 13,14 It is, therefore, expected that the dielectric investigations of MgB 2 may shed some lights on the intergrain properties. Unfortunately, most of the existing reports on dielectric properties of MgB 2 were measured on microwave and optical frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…For a clear comparison, the previously reported susceptibilities χ a , χ b , and χ c of the single crystals of CuO, and that of a random-oriented polycrystalline CuO are re-plotted in Fig. 2a [9]. From the figure, one can see small decreases at T N1 and drastic drop and jump in χ b and χ c at T N2 , respectively.…”
Section: Methodsmentioning
confidence: 76%
“…Zheng et al found hole ordering in striped domains analogous to the charge stripes in cuprates [7], and further found that there exists a strong charge-spin-lattice coupling and a possible Cu orbital coupling contributing to the short-range antiferromagnetic interaction up to 800 K, where a charge-spin-lattice correlated phase transition featured by charge excitation, specific heat anomaly and decrease in lattice distortion was verified [8]. They also observed ferroelectric properties in this strongly magnetic-dielectric coupled material [9]. In recent years, magnetism induced-ferroelectricity in CuO has been grouped into multiferroics with high Curie temperature T C [10].…”
Section: Introductionmentioning
confidence: 73%
“…CuO is of high-T C multiferroic phase between 213 K and 230 K, which is different from other conventional magnetic-induced multiferroics with low-T C (T C <100 K), such as RMnO 3 and RMn 2 O 5 (R= Tb, Dy, etc) [2,[6][7][8][9]. At room temperature, CuO belongs to C2/c space group and has a monoclinic structure (a=4.69 Å, b=3.42 Å, c=5.13 Å; β=99.5°) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cupric oxide (CuO), known as the parent compound of high T C superconductor, was recently reported as magnetic-induced multiferroics [6][7][8]. CuO is of high-T C multiferroic phase between 213 K and 230 K, which is different from other conventional magnetic-induced multiferroics with low-T C (T C <100 K), such as RMnO 3 and RMn 2 O 5 (R= Tb, Dy, etc) [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%